2021
DOI: 10.1136/jim-2020-001714
|View full text |Cite
|
Sign up to set email alerts
|

Gout as a Risk Factor for Acute Myocardial Infarction: Evidence from Competing Risk Model Analysis

Abstract: Chronic inflammation, a hallmark of gout, is implicated in the pathogenesis of atherosclerosis. Thus, in theory, gout can be expected to increase the risk of acute myocardial infarction (AMI). Yet, results from several epidemiological studies have been inconclusive. A retrospective cohort study was conducted using the National Health Insurance Research Database of Taiwan dated from 2000 to 2013. The study cohort comprised 3581 patients with gout (the gout cohort) and 14,324 patients without gout (the non-gout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Besides the increased personal financial burden, direct and indirect annual financial burdens exist for those who cannot control gout well [ 3 ]. Patients with cardiovascular disease who have also been diagnosed with gout have higher mortality rates, regardless of age, sex, and comorbidities factors [ 4 ]. The mortality gap of gout, which is the association with premature death, has stayed consistent over 2 decades [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the increased personal financial burden, direct and indirect annual financial burdens exist for those who cannot control gout well [ 3 ]. Patients with cardiovascular disease who have also been diagnosed with gout have higher mortality rates, regardless of age, sex, and comorbidities factors [ 4 ]. The mortality gap of gout, which is the association with premature death, has stayed consistent over 2 decades [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 408 443 GA patients and 10 402 777 non‐GA patients were included in the meta‐analysis. The basic characteristics of the 11 selected cohort studies in the meta‐analysis are shown in Table 1 4,8–10,14,21–26 . All the studies were cohort studies, and the studies were published between 2006 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…The basic characteristics of the 11 selected cohort studies in the meta-analysis are shown in Table 1. 4,[8][9][10]14,[21][22][23][24][25][26] All the studies were cohort studies, and the studies were published between 2006 and 2020. There are 9 articles and 10 studies on the correlation between GA and MI risk, and there are 4 articles and 5 studies on the risk of GA and HF.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether gout itself is a risk factor for cardiovascular diseases and whether the risk of cardiovascular diseases is increased by comorbidities such as hypertension, diabetes, and hyperlipidemia remain controversial. Huang et al [8] have applied propensity score (PS) matching to answer this. Even after PS matching of comorbidities (i.e., hypertension, diabetes, hyperlipidemia, and CVD etc.…”
Section: Discussionmentioning
confidence: 99%